EXTH-68. STUDY THE SYNERGISTIC EFFECT OF FOCUSED ULTRASOUND AND RADIATION THERAPY FOR BRAIN TUMOR TREATMENT - Huang, Chiungyin (Neuro Oncol, 2020)
The standard treatment of malignant brain tumor is surgical resection followed by adjuvant chemo/radiotherapy. However, in spite of these aggressive treatments, tumor may still recur and resulting in poor survival. In solid tumors, the hypoxia condition presented in most of tumor area may contribute to treatment failure in both adjuvant therapies. It had been proven that systemic delivered oxygen may not sufficient for ionizing radiation to produce cytotoxic effect. A recent study reported using focused ultrasound combined with oxygen-contained microbubbles prior to radiation significantly increased the oxygen content in breast cancers and statistically improved animal survival. Therefore, providing sufficient oxygen in tumor area may be beneficial for radiation therapy. To study the potential role of such strategy for brain tumor treatment, we used focused ultrasound to treat brain tumor bearing animals before radiation therapy. As compared with non-ultrasound treatment groups, the tumor growth rate was significantly inhibited, and the animal survival is prolonged. We also analysis the gene expression changes, reveal some potential pathway that may involve in the process. Furthermore, we found focused ultrasound combined with non-oxygen-containing microbubbles also represented similar results, demonstrate the focused ultrasound induced cerebral vascular permeability increment may also contribute to the radiation therapy effect for brain tumor treatment.